PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MENINGKATKAN KETRAMPILAN BERPIKIR KRITIS DAN PEMAHAMAN PKn - Tutut Zatmiko; Darsono Darsono; Irawan Suntoro (Faculty of Teacher Training and Education, University of Lampung, 2015)
This research aimed to improve the lesson plan, the implementation of learning, the students critical thinking skills, and students' understanding of civics through social PBL models. This research was a classroom action research by using three cycles. The subject of research were students in grade X MIA 1 and X MIA 2. The data were collected by observation and tests and analyzed by descriptive analysis. The result of research: 1) the students instructional design was in accordance with the results of the analysis of the needs of the poor critical thinking skills and students understanding of civics, 2) the activity of students in the learning process were the teachers guide students to analyze and evaluate the process of solving the problem, 3) the ability of critical thinking of students was increased in each cycle, and 4) students' understanding of civics has also increased each cycle.Penelitian ini bertujuan untuk meningkatkan perencanaan pembelajaran, meningkatkan pelaksanaan pembelajaran, meningkatkan keterampilan berpikir kritis siswa, dan meningkatkan pemahaman PKn siswa melalui model PBM sosial. Penelitian merupakan penelitian tindakan kelas dengan mengunakan tiga siklus. Subjek penelitian siswa kelas X MIA 1 dan X MIA 2. Pengumpulan data melalui observasi dan tes serta dianalisis secara deskriptif analisis. Hasil penelitian: 1) desain pembelajaran sesuai dengan hasil analisis kebutuhan tentang rendahnya kemampuan berpikir kritis dan pemahaman PKn siswa, 2) aktivitas siswa dalam proses pembelajaran adalah guru membimbing siswa untuk menganalisis dan mengevaluasi proses pemecahan masalah, 3) kemampuan keterampilan berpikir kritis siswa mengalami peningkatan setiap siklusnya, dan 4) pemahaman siswa tentang PKn juga meningkat setiap siklusnya.Kata kunci: keterampilan berpikir kritis, pbm sosial, pkn